Reflections on Kenneth E. Boulding’s The Image: Glimpsing the Roots of Peace Education Pedagogy (In Factis Pax: Journal of Peace Education and Social Justice, 2013)
The March/April 2013 issue of the Global Campaign for Peace Education newsletter features a reflection on the evolution of the field of peace education in the spotlight of the nomination of Betty Reardon, renowned peace educator, for the 2013 Nobel  Peace Prize. The article notes that the field of peace education, in its early years, “was viewed by research scholars and peace activists as a positive complement to, but not an essential and integral part of the larger movement.” This marginalization of the field, and general separation of areas of peace knowledge (research, studies, education, activism), is a major obstacle impeding possibilities for transdisciplinary efforts to cooperatively and collaboratively affect and transform systems and cultures of violence.